ISLEX: Islandsk-skandinavisk webordbog. - Jónsdóttir, Halldóra; Úlfarsdóttir, Þórdís Úlfarsdóttir (Nordiske Studier i Leksikografi, 2007)
ISLEX is a multilingual dictionary with modern Icelandic as source language and Danish, Norwegian and Swedish as target languages. The project is a collaboration of four institutes in the Nordic countries with a central base in Reykjavík, Iceland. With 50.000 entry words, ISLEX is a medium sized dictionary. Set in a custom-made relational database, it is designed as an on-line dictionary where the various possibilities of the web are utilised. So ISLEX has pictures and animated images, and pronunciation given as sounds. There is a special emphasis on Icelandic phrases and fi xed epressions, all of which are translated into the three target languages. The work on the dictionary takes place simultaneously in four countries. The processing of the base language and coordination is based in Iceland, the Danish translation team is located in Denmark, the Norwegian team in Norway, and the Swedish team in Sweden. ISLEX is a six year project, begun in 2005. The aim is to complete the dictionary in mid-year 2011.